2020
DOI: 10.1002/smtd.202000356
|View full text |Cite
|
Sign up to set email alerts
|

Selective Sensing of Proteins Using Aptamer Functionalized Nanopore Extended Field‐Effect Transistors

Abstract: The ability to sense proteins and protein-related interactions at the singlemolecule level is becoming of increasing importance to understand biological processes and diseases better. Single-molecule sensors, such as nanopores have shown substantial promise for the label-free detection of proteins; however, challenges remain due to the lack of selectivity and the need for relatively high analyte concentrations. An aptamer-functionalized nanopore extended field-effect transistor (nexFET) sensor is reported here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 53 publications
0
48
0
Order By: Relevance
“…In this regard, the application of nanopores has not been limited to DNA sequencing and functionalized nanopores have been shown to be effective in high-speed single-molecule detection of proteins. FET-equipped, aptamer-functionalized nanopores have been used to detect human thrombin protein by Ren et al (2020). However, ensuing experimental investigations implied a different physics at work in these devices (Xie et al , 2012; Traversi et al , 2013) than that outlined above.…”
Section: Nanopore Sensing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the application of nanopores has not been limited to DNA sequencing and functionalized nanopores have been shown to be effective in high-speed single-molecule detection of proteins. FET-equipped, aptamer-functionalized nanopores have been used to detect human thrombin protein by Ren et al (2020). However, ensuing experimental investigations implied a different physics at work in these devices (Xie et al , 2012; Traversi et al , 2013) than that outlined above.…”
Section: Nanopore Sensing Methodsmentioning
confidence: 99%
“…In this regard, the application of nanopores has not been limited to DNA sequencing and functionalized nanopores have been shown to be effective in high-speed single-molecule detection of proteins. FET-equipped, aptamer-functionalized nanopores have been used to detect human thrombin protein by Ren et al (2020).…”
Section: Nanopore Sensing Methodsmentioning
confidence: 99%
“…31 To overcome these limitations, several alternative nanopore sensing strategies have been proposed and demonstrated. One such technique relies on integrating nanoelectrode structures such as field-effect sensors 31,[67][68][69][70][71] and electron tunnelling nanogaps [72][73][74][75][76] with a nanopore. Changes in the current through these nanoelectrode structures occur as a result of analytes translocating through an integrated or nearby nanopore.…”
Section: Solid State Nanoporesmentioning
confidence: 99%
“…Moreover, it offers a route towards selective biomolecular detection. 71,150,151 It was recently demonstrated that adding NaClO to the solution during CBD resulted in a significant change in the nanopore surface charge even after the electrolyte was replaced. 152 For DNA translocation experiments, this change in the surface charge resulted in an increased event frequency and less pore clogging due to reduced electrostatic interactions between the pore walls and the translocating molecule.…”
Section: Advantages Of Controlled Breakdownmentioning
confidence: 99%
“… 4 An addition to the resistive pulse sensing method is a variety of sensing modalities that solid-state nanopores (SSNPs) can offer, including multicolor discrimination of labeled DNAs and polypeptides, 5 , 6 ultrasensitive detection of proteins using nanopore blockade sensors, 7 optical profiling based on local plasmonic effect, 8 and selective sensing with nanopore-extended field-effect transistors. 9 , 10 Compared to their biological counterparts, the remarkable versatility of SSNPs is due to their wide-range tunability in pore geometries and dimensions as well as mechanical robustness and stability. An added advantage with SSNPs is the compatibility of their fabrication with control electronics as well as optical measurement structures.…”
Section: Introductionmentioning
confidence: 99%